Perbandingan Kinerja Keuangan Berdasarkan Income Statement Approach dan Value Added Approach pada PT. Bank Syariah Indonesia Tbk. - Sri Indah Sari; Hajrah Hamzah; Warka Syachbrani (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
Comparison of Financial Performance Based on Income Statement Approach and Value Added Approach at PT. Bank Syariah Indonesia Tbk. Thesis. Bachelor's Program in Accounting, Faculty of Economics and Business, Universitas Negeri Makassar. Advisors: Hajrah Hamzah, S.E., M.Si., Ak. CA., and Warka Syachbrani, SE., M.Sc., Ak., CA. This study aims to analyze the comparison of financial performance using the Income Statement Approach (ISA) and Value Added Approach (VAA) at PT. Bank Syariah Indonesia Tbk. The research adopts a quantitative method with a descriptive approach. The population of this study is the financial reports of PT. Bank Syariah Indonesia Tbk., while the sample comprises annual reports from 2021 to 2023. The descriptive analysis shows that the average financial performance ratios based on VAA are higher than those based on ISA, with the following details: ROA: 0.014 (ISA) vs. 0.026 (VAA), ROE: 0.132 (ISA) vs. 0.253 (VAA), NPM: 0.283 (ISA) vs. 0.539 (VAA). Hypothesis testing using the Independent Sample T-test indicates significant values for each ratio (ROA: 0.002; ROE: 0.004; NPM: 0.007), all below 0.05, thus supporting the proposed hypothesis. These findings suggest significant differences in financial performance measured using the two approaches. This study concludes that the VAA approach provides a more comprehensive perspective compared to ISA, as it reflects the distribution of value added to various stakeholders, not only shareholders.